Mucopolysaccharidosis type VI: case report with first neonatal presentation with ascites fetalis and rapidly progressive cardiac manifestation - Rachel Sayuri Honjo; Evelyn Cristina Nuñez Vaca; Gabriela Nunes Leal; Deipara Monteiro Abellan; Nana Miura Ikari; Marcelo Biscegli Jatene; Ana Maria Martins; Chong Ae Kim (BMC, 2020)
Abstract Background The Mucopolysaccharidosis type VI (MPS VI), also known as Maroteaux-Lamy syndrome (OMIM 253200) is an autosomal recessive lysosomal disorder, caused by the deficiency of the enzyme N-acetylgalactosamine 4-sulfatase (also known as arylsulfatase B) due to mutations of the ARSB gene. Cardiologic features are well recognized, and are always present in MPS VI patients. Generally, the onset and the progression of the cardiologic symptoms are insidious, and just a few patients have developed a rapidly progressive disease. Cardiac involvement in MPS VI is a common and progressive feature. For MPS patients, cardiac evaluations are recommended every 1 to 2 years, including blood pressure measurement, electrocardiography and echocardiography. However, congestive heart failure and valvular surgical repair are not frequently seen, and if so, they are performed in adults. Here we report on an atypical MPS VI case with ascites fetalis and a rapidly progressive cardiac disease. Case presentation A 6-month-old Brazilian male, only child of a Brazilian healthy non-consanguineous couple. During pregnancy, second trimester ultrasonography observed fetal ascites and bilateral hydrocele. Physical exam at 6 months-old revealed a typical gibbus deformity and MPS was suspected. Biochemical investigation revealed a diagnosis of MPS type VI, confirmed by molecular test. Baseline echocardiogram revealed discrete tricuspid regurgitation and a thickened mitral valve with posterior leaflet prolapse, causing moderate to severe regurgitation. The patient evolved with mitral insufficiency and congestive heart failure, eventually requiring surgical repair by the first year of age. Conclusions We report the first case of MPS VI whose manifestations started in the prenatal period with fetal ascites, with severe cardiac valvular disease that eventually required early surgical repair. Moreover, in MPS with neonatal presentation, including fetal hydrops, besides MPS I, IVA and VII, clinicians should include MPS VI in the differential diagnosis.